Ethical Decision-Making Theory: An Integrated Approach - Schwartz, Mark S. (Journal of business ethics, 2016)
Ethical decision-making (EDM) descriptive theoretical models often conflict with each other and typically lack comprehensiveness. To address this deficiency, a revised EDM model is proposed that consolidates and attempts to bridge together the varying and sometimes directly conflicting propositions and perspectives that have been advanced. To do so, the paper is organized as follows. First, a review of the various theoretical models of EDM is provided. These models can generally be divided into (a) rationalist-based (i.e., reason); and (b) non-rationalist-based (i.e., intuition and emotion). Second, the proposed model, called ‘Integrated Ethical Decision Making,’ is introduced in order to fill the gaps and bridge the current divide in EDM theory. The individual and situational factors as well as the process of the proposed model are then described. Third, the academic and managerial implications of the proposed model are discussed. Finally, the limitations of the proposed model are presented.